The Effect of Research and Development (R&D) Investment, E-Commerce Company Employee, and E-Commerce Transaction Volume on Economic Growth in Indonesia 2010Q1 – 2020Q4 - Gebrella Nadia Sumahir; Heru Wahyudi; Tiara Nirmala (Pustaka Peradaban, 2022)
This study aims to analyze the effect of R&D investment, the volume of e-commerce transactions, and e-commerce companies employee on economic growth in Indonesia for the period 2010Q1 – 2020 Q4. The analytical method used in this study is OLS (Ordinary Least Square) anda method using time series data in the form of quarterly from 2010 to 2020. In conducting this research the author uses the help of the E-views 9 analysis tool. The results of this study are that the variables of R&D investment, e-commerce companies employee, and the volume of e-commerce transactions have a partial or joint effect on economic growth in Indonesia in 2010 Q1 to 2020 Q4.